Civil liability of the Bank for Deposits Received: A Comparative Study - Mezher, Haneen; Ameen, Khalis (Journal of Legal Sciences, 2023)
Because bank deposits, whether cash deposits or securities deposits, entail obligations on the bank, it is natural that violating these obligations results in the realization of its civil responsibility, and responsibility in its general meaning is culpability and liability. The source of this obligation was the agreement or the law, and the work of the rules of civil liability is based on the availability of three pillars, which are the error, the damage and the causal relationship between them, and as long as the bank deposit is a contract, the responsibility of the bank in the event of a breach of one of the obligations arising from this contract is definitely a contractual responsibility, but it may be imagined The establishment of tort liability in cases we will explain when talking about cases of civil liability of the bank, but trends have emerged that the bank’s responsibility, according to the nature of the activity it practices, which is banking and its importance, has entered it within the scope of professional responsibility based on professional error, while there is another trend that goes To be satisfied with the element of harm, i.e. on the basis of the idea of ​​risks and bearing the consequences, they consider that the harm caused to work That alone is sufficient to realize the responsibility of the bank, regardless of the error and the causal relationship between them.